2020
DOI: 10.3390/genes11020127
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Expression Profile of the TIFY Gene Family in Brassica oleracea var. capitata, and Their Divergent Response to Various Pathogen Infections and Phytohormone Treatments

Abstract: TIFY, a plant-specific gene family with the conserved motif TIF[F/Y]XG, plays important roles in various plant biological processes. Here, a total of 36 TIFY genes were identified in the Brassica oleracea genome and classified into JAZ (22 genes), TIFY (7 genes), ZML (5 genes), and PPD (2 genes) subfamilies based on their conserved motifs, which were distributed unevenly across nine chromosomes with different lengths (339–1077 bp) and exon numbers (1–8). Following phylogenetic analysis with A. thaliana and B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 83 publications
7
45
0
Order By: Relevance
“…TIFY proteins have proven to be important regulators in abiotic and biotic stress responses in plants. Since the Arabidopsis JAZ subfamily was identified as the vital repressor in JA signaling, increasing numbers of other JAZ proteins have been characterized as important stress-response regulators in various plant species, including B. rapa, B. oleracea, rice, cotton, tomato, poplar, grape, soybean, wheat, maize, rubber tree, Moso bamboo and purple false brome [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][55][56][57]. However, no B. napus TIFY was isolated and identified over the whole genome.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TIFY proteins have proven to be important regulators in abiotic and biotic stress responses in plants. Since the Arabidopsis JAZ subfamily was identified as the vital repressor in JA signaling, increasing numbers of other JAZ proteins have been characterized as important stress-response regulators in various plant species, including B. rapa, B. oleracea, rice, cotton, tomato, poplar, grape, soybean, wheat, maize, rubber tree, Moso bamboo and purple false brome [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][55][56][57]. However, no B. napus TIFY was isolated and identified over the whole genome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that a total of 36 and 36 TIFY proteins were identified in B. rapa accession Chiifu-401-42 [ 51 ] and B. oleracea var. capitate lines (02–12 and D134) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations